2011
DOI: 10.1161/strokeaha.110.606293
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Preventing the Interaction of Tissue-Type Plasminogen Activator With N-Methyl- d -Aspartate Receptors Reduce Stroke Damages and Extend the Therapeutic Window of Thrombolysis

Abstract: Our strategy limits ischemic damages and extends the therapeutic window of tPA-driven thrombolysis. Thus, the prospect of this immunotherapy is an extension of the range of treatable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
3
45
0
5
Order By: Relevance
“…20 In addition, thrombolysis performed as for patients with stroke (10% bolus and 90% infusion >1 hour) also has a therapeutic window, with early recanalization being beneficial but not if performed too late. 21,22 Whether thrombin exerts specific effects on the neurovascular unit 23,24 beside clot formation in this model remains to be established.…”
Section: Alcohol Consumption Impairs the Beneficial Effect Of Tpa-indmentioning
confidence: 99%
“…20 In addition, thrombolysis performed as for patients with stroke (10% bolus and 90% infusion >1 hour) also has a therapeutic window, with early recanalization being beneficial but not if performed too late. 21,22 Whether thrombin exerts specific effects on the neurovascular unit 23,24 beside clot formation in this model remains to be established.…”
Section: Alcohol Consumption Impairs the Beneficial Effect Of Tpa-indmentioning
confidence: 99%
“…As previously described, 22 thrombotic stroke was induced by injecting thrombin (1.0 IU in 1 L) directly in the middle cerebral artery. To induce thrombolysis, rtPA was intravenously injected (tail vein, 200 L, 10 mg/kg, 10% bolus and 90% infusion over 40 minutes) either at 4 hours or 20 minutes postclot onset 15 with or without an intravenous bolus of memantine (200 L, 20 mg/kg) just before rtPA infusion. Control groups received the same volume of saline with or without memantine (nϭ7-8 per group).…”
Section: Thrombotic Stroke Model and Thrombolysismentioning
confidence: 99%
“…22 In this model, early thrombolysis by rtPA (20 minutes postonset) is beneficial, whereas late thrombolysis (4 hours postonset) is deleterious. 15 The effect of intravenous memantine (20 mg/kg, a dose chosen based on the literature 24 ) as an adjunct treatment to late thrombolysis by rtPA was thus tested. T2-weighted MR images at 6, 24, and 48 hours after stroke ( Figure 3A) revealed that although memantine did not alter the extent of the ischemic damage in the absence of rtPA ( Figure 3B Although the deleterious effects of delayed thrombolysis appeared at 6 hours postclot onset and continued to progress between 24 and 48 hours, the lesion volumes of control, memantine, and memantine/rtPA-treated groups reached their maximum at 24 hours ( Figure 3A-B).…”
Section: Memantine Reduces the Noxious Actions Of Delayed Thrombolysimentioning
confidence: 99%
See 1 more Smart Citation
“…6 Activation of NMDAR has been suggested as a possible mechanism of tPA-dependent neuroprotection following OGD in cortical neurons, 20 but we did not confirm these results in our present model. This may be explained by the use of different strategies to block tPA-dependent NMDAR signaling, that is, MK-801 as a broad antagonist of NMDAR on one hand and an antibody previously characterized to specifically prevent the tPA-dependent potentiation of NMDAR signaling without affecting their basal activity 30 on the other hand. Although LRP was also reported to mediate some of the neuroprotective functions of tPA, 31 we excluded its implication in our models using RAP, a well-characterized antagonist of the interaction of tPA with LRP.…”
Section: Discussionmentioning
confidence: 99%